2019
DOI: 10.5194/gmd-12-5229-2019
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity studies with the regional climate model COSMO-CLM 5.0 over the CORDEX Central Asia Domain

Abstract: Due to its extension, geography and the presence of several underdeveloped or developing economies, the Central Asia domain of the Coordinated Regional Climate Downscaling Experiment (CORDEX) is one of the most vulnerable regions on Earth to the effects of climate changes. Reliable information on potential future changes with high spatial resolution acquire significant importance for the development of effective adaptation and mitigation strategies for the region. In this context, regional climate models (RCMs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 103 publications
10
33
0
2
Order By: Relevance
“…This fact could be related to the interaction of the microphysical scheme with the association of PBL (MYJ) scheme, which is in line with other studies with higher precipitation totals and more convective precipitation [89,90]. Additionally, for precipitation over areas of complex topography, wet bias is particularly found to be common to several RCMs [91,92], and is probably caused by an overestimation of orographic precipitation enhancement [93], and/or to an inaccurate PBL simulation [7,11,94]. The Taylor diagrams shown in Figure 3 provide the comparative assessment of the four different model experiments to the choice of the physical parameterizations, to simulate the seasonal spatial pattern of daily precipitation during the examined period.…”
Section: Precipitationsupporting
confidence: 85%
See 1 more Smart Citation
“…This fact could be related to the interaction of the microphysical scheme with the association of PBL (MYJ) scheme, which is in line with other studies with higher precipitation totals and more convective precipitation [89,90]. Additionally, for precipitation over areas of complex topography, wet bias is particularly found to be common to several RCMs [91,92], and is probably caused by an overestimation of orographic precipitation enhancement [93], and/or to an inaccurate PBL simulation [7,11,94]. The Taylor diagrams shown in Figure 3 provide the comparative assessment of the four different model experiments to the choice of the physical parameterizations, to simulate the seasonal spatial pattern of daily precipitation during the examined period.…”
Section: Precipitationsupporting
confidence: 85%
“…This fact could be related to the interaction of the microphysical scheme with the association of PBL (MYJ) scheme, which is in line with other studies with higher precipitation totals and more convective precipitation [88,89]. Additionally, for precipitation over areas of complex topography, wet bias is particularly found to be common to several RCMs [90,91], and is probably caused by an overestimation of orographic precipitation enhancement [92], and/or to an inaccurate PBL simulation [7,11,93].…”
Section: Precipitationsupporting
confidence: 83%
“…for the cold biases in the northwest and over the mountain ranges. Similar biases to those of ALARO-0 in summer were found by Russo et al (2019) with the RCM COSMO-CLM 5.0. In spring and summer both RCMs show a pronounced warm bias over Pakistan and the northern part of India and there is also a north-south gradient from cold to warm biases over the Arabian Peninsula.…”
Section: Mean Temperaturesupporting
confidence: 80%
“…Giot et al (2016) suggested this could be due to the strong synoptic scale forcing in winter and stable boundary layer issues. A warm bias during winter in the northeastern part of the domain was found as well by Russo et al (2019) and Ozturk et al (2012 and for the COSMO-CLM 5.0 and RegCM models, respectively. Furthermore, Fig.…”
Section: Mean Temperaturementioning
confidence: 64%
See 1 more Smart Citation